Social determinants of covid-19 mortality: The Peruvian case - César Cipriano Zea-Montesinos; Olga Vicentina Pacovilca-Alejo; Gelber Sebasti Pacovilca-Alejo; José Santiago Almeida-Galindo; Zaida Zagaceta-Guevara; Héctor Vicehich Millán-Camposano; Melisa Pamela Quispe-Ilanzo; Alfredo Enrique Oyola-García (Universidad de Ciencias Médicas de La Habana, 2024)
Introduction: The impact of the COVID-19 pandemic has been very different in terms of morbidity and mortality, even among those territories with similar socioeconomic conditions and political backgrounds. Objective: To identify social determinants of socio-geographic inequality from COVID-19 mortality in Peru during the first year of pandemic. Material and Methods: Observational ecological research, based on the secondary analysis of mortality by COVID-19 during the year 2020 in the subnational governments of Peru. Results: The percentage of the population registered with social security was the only variable with statistical significance (t=2.921; p=0.008) that explained GMR due to COVID-19 (F=21.360; p=0.000). Adequate employment was the only variable with statistical significance (t=3.018; p=0.006) that explained SMR due to COVID-19 (F=18.910; p=0.000). The excess GMR and SMR due to COVID-19 amounted to 227.93 and 138.76 deaths per 100,000 inhabitants along the social gradient determined by the population enrolled in social security and those with adequate employment, respectively. Conclusions: The percentage of the economically active population with adequate employment, which is mainly under the social security, would have been the social determinant of the socio-gepgrphic inequality in COVID-19 mortality between the different subnational governments of Peru during the first year of the pandemic.